Ebola virus disease: epidemiology, clinical features and the way forward - Balami, Lawan Gana; Ismail, Suriani; S. M., Saliluddin; S. H., Garba (Medip Academy, 2017)
The Ebola virus disease is a zoonotic, acute viral syndrome which occurs by infection with one the strains of the Ebola virus. It is primarily endemic in Africa however the recent outbreak in the year 2014 spanned from West Africa all the way to Europe and America. This shows the virus possess a global threat and should not be considered localized to only certain parts of the world. The social and economic impact of zoonotic diseases today is high as 80% of human pathogens are of zoonotic origin. Human to human transmission happens when there is contact with bodily fluids of infected humans during the infectious phase of the disease. This spread could be through nosocomial means or community spread. Poor knowledge of the syndrome among health care workers coupled with lack of funding and deficient resources has crippled their ability to diagnose and break the chain of transmission of the disease at its early stages. The virus undergoes pathogenesis by immune evasion, immune suppression, coagulopathy, and hypovolemic shock, multiple organ failure and death in up to 90% of cases. The unavailability of a cure or vaccine for this syndrome makes it a recurrent threat due to high risk behavior practiced in endemic countries such as bush meat consumption. Thus this study gives the reader a review of current literature on this deadly disease with the aim of increasing knowledge and aiding its prevention and control.